Facile synthesis of (E)-β-nitroolefinic alkoxyamines via silver-catalyzed decarboxylative nitroaminoxylation of phenylpropiolic acids1. Issue 5 (12th May 2015) - Yan, Hong; Mao, Jincheng; Rong, Guangwei; Liu, Defu; Zheng, Yang; He, Yue
<x xml:space="preserve">Abstract</x> A novel silver-catalyzed decarboxylative nitroaminoxylation reaction of phenylpropiolic acids is described, leading to (E)-β-nitroolefinic alkoxyamines.